Bridging Languages and Faith: A Pictorial Approach to Teaching Basic Islam to Bilingual Children - Zakaria, Muhamad Khairul; Wan Salam, Wan Nurhafeza; Basir, Mohammad Aizat; Ayub, Alyani; Mamat, Mohd Zulkanain; Embong, Abdul Mutalib; Ab Wahab, Noor Azida; Mohd Zaini, Muhammad Mursyid; Md. Aris, Nur Azlina; Nugroho, Catur; Hussain, Juliani; Muhamad, Md Khairil Hafizi; Kadhim, Kais Amir (Scientia Publica Media, 2026)
Bilingual children often encounter greater challenges in school than their monolingual peers, particularly when dealing with abstract concepts and religious education. Teaching the fundamentals of Islam in English is difficult due to the limited availability of locally relevant resources. To address this gap, “My First Handbook of Islam” was developed through four stages involving Islamic scholars, linguists, educators, and illustrators. The book was distributed to schools and Islamic centres, with 1,100 copies disseminated nationally and internationally. This study assessed bilingual children’s attitudes toward the book using a descriptive, quantitative, cross-sectional survey. A total of 104 bilingual children aged 10 to 12 participated, recruited through convenience sampling with parental consent. The instrument consisted of structured questionnaire items (5-point Likert scale), covering vocabulary, comprehension, engagement, sharing, and motivation. The tool achieved good internal reliability (Cronbach’s alpha = 0.82). Data were collected through paper-based surveys, supervised in classrooms after guided reading sessions, and analysed using SPSS v27. Descriptive statistics (frequency, percentage, mean) were applied, with interpretation guided by mean scales. Findings showed that students unanimously valued the book, reporting improved vocabulary acquisition, enthusiasm for Islamic knowledge, and enjoyment of illustrations. The pictorial approach bridged language gaps, reduced cognitive load, and increased engagement through culturally relevant visuals. The book was also used for sharing knowledge with siblings, peers, and teachers, though less so with parents due to language mismatches. The study concludes that pictorial Islamic texts are effective for bilingual learning and can be further enhanced through integration into digital formats such as interactive e-books and mobile apps. Implications are drawn for teachers, parents, curriculum designers, and Islamic educational institutions, especially in multicultural settings.